Scanning Probe Microscopy for polymer film characterization in food packaging. (May 2019) - Marinello, F; Pezzuolo, A; Passeri, D; La Storia, A; Mauriello, G
Abstract: Scanning probe microscopy (SPM) is a branch of microscopy allowing characterization of surfaces at the micro-scale by means of a physical probe (with a size of a few microns) raster scanning the sample. SPMs monitor the interaction between such probe and the surface and, depending on the specific physical principles causing the interaction, they allow generation of a quantitative map of topographic properties: geometrical, optical, electrical, magnetic, etc. This is of the greatest interest, in particular whenever functional surfaces have to be characterized in a quantitative manner. The present paper discusses the different applications of Scanning Probe Microscopy techniques for a thorough characterization of polymer surfaces, of specific interest in particular for the case of food packaging applications.